Food and beverage (F&B) mobile application for Burger King restaurant / Siti Nurul Sakinah Harun - Harun, Siti Nurul Sakinah (2013)
Smart phone has become a trend to most of the people these days as a lot of tasks can be done with it. People can browse the internet, email, social networking, and do business transaction anytime and anywhere. Therefore, Burger King, a fast food chain proposes a web-based mobile application for their fast food delivery services. The current method used by customers to place their orders is by making a phone call. However, the method is time consuming during peak hours and causes a lot of mistakes during ordering take place. Thus, Food and Beverage (F&B) Mobile Application is being proposed to provide fast food delivery ordering via mobile for the customers. The users can view the menus and place their orders with this application. They can also track the status of their order and locate the nearest Burger King's store. Moreover, this application also allows users to email their feedback to the company. The implementation of this mobile application will bring greater mobility, convenience and accessibility to customers. The system architecture to design this system are XAMPP server, HTML5, Java Script and PHP as programming language, supported with Phone Gap framework and MySQL as database.